A United Description for Dark Matter and Dark Energy - On, Vo Van (Communications in Physics, 2019)
In this paper, we show a unifying description to the dark matter and dark energy. This description does not demand dark energy with the anti-gravitational property. It also points out a lower limit of the average mass of the particles of cosmological energy (ordinary matter, dark matter and dark energy particles) \(\bar{m}\gg 54\) eV. The coincident problem between the density of dark energy and one of matter is a clear fact.